2020
DOI: 10.1186/s41235-020-00262-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in susceptibility to false memories for COVID-19 fake news

Abstract: Exposure to ‘fake news’ can result in false memories, with possible consequences for downstream behaviour. Given the sharp rise in online misinformation during the coronavirus pandemic, it is important to understand the factors that influence the development of false memories. The present study measured susceptibility to false memories following exposure to fabricated news stories about the pandemic in a sample of 3746 participants. We investigated the effect of individual differences in (1) knowledge about CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 33 publications
13
69
3
3
Order By: Relevance
“…Future research should examine whether executive functions also influence the accuracy of recalling content about the future. It would also be interesting to analyze individual differences (especially in the older group) in positivity bias because there may be great variability, as with other types of false memories ( Gerrie and Garry, 2007 ; St Jacques et al, 2015 ; Greene and Murphy, 2020 ). The investigation of the particularities of cognitive functioning and memory of middle-aged adults is relevant from a cognitive research perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should examine whether executive functions also influence the accuracy of recalling content about the future. It would also be interesting to analyze individual differences (especially in the older group) in positivity bias because there may be great variability, as with other types of false memories ( Gerrie and Garry, 2007 ; St Jacques et al, 2015 ; Greene and Murphy, 2020 ). The investigation of the particularities of cognitive functioning and memory of middle-aged adults is relevant from a cognitive research perspective.…”
Section: Discussionmentioning
confidence: 99%
“…As in many prior studies, the current research presents evidence that individuals can form false memories and beliefs for fabricated events. Research has identified a number of factors that may increase susceptibility towards false memories and beliefs in response to misinformation, including age, cognitive ability, subject knowledge, and analytical reasoning (Greene & Murphy, 2020; Roediger & Geraci, 2007; Zhu et al, 2010). The current study contributes to growing evidence that partisanship may also be a predictor of susceptibility to fabricated political stories (Frenda et al, 2013; Greene et al, 2021; Murphy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Though the current study used a simple paradigm for assessing false memories for political events that has been utilised in similar studies (Frenda et al, 2013; Greene & Murphy, 2020), we are limited in our understanding of how rich these recollections were. Future research might examine this political congruency effect in a manner that allows for deeper exploration of the phenomenology of these memories, such as interviews or using a longitudinal design to assess the memories over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking back to the distinction made earlier between task-specific, domain-specific, and domain-general effects, all of the evidence considered in this section falls squarely within the purview of task-specific effects, ie, photos and Internet headlines can produce distorted or entirely false memories for a specific event, but there is no evidence that they produce broader changes such that people are more generally susceptible to suggestion and misattribution as a consequence of exposure to these forms of media. We do know that some individuals are more susceptible than others to particular kinds of false memories attributable to misinformation (eg, Zhu et al 2010), semantic associations (eg, Clancy et al 2000;Dewhurst et al 2018), and fake news about the Covid-19 pandemic (Greene and Murphy 2020). However, in a study that examined participants' performance on three well-established laboratory false memory tasks, Nichols and Loftus (2019) failed to find evidence that some individuals are consistently more prone to false memories across the three tasks.…”
Section: Misattribution and Suggestibilitymentioning
confidence: 99%